ASSESSING CIRCULAR ECONOMY PERFORMANCE OF EUROPEAN COUNTRIES AND SERBIA USING DATA ENVELOPMENT ANALYSIS - Marcikic Horvat, Aleksandra; Radovanov, Boris; Stojić, Dragan; Sedlak, Otilija; Bobera, Dušan (The European Journal of Applied Economics, 2023)
The circular economic system concentrates on closing the loop for resource flows by imitating the function of natural ecosystems in order to achieve sustainability. The purpose of this study is to present a comprehensive approach to assessing countries’ performance in municipal waste management and utilization. This paper assessed the change in the efficiency of circular economy performance over the period of four years, from 2016 until 2019. In the first stage, output-oriented DEA model with a variable return to scale has been applied, while in the second stage Tobit regression model examined the influence of macroeconomic factors on achieved efficiency scores. Results show that the performance of the circular economy has an enviable level of efficiency since the average score is above 70%. Belgium, Lithuania, Poland and Sweden achieved extremely high-efficiency levels during the whole time frame. Countries with the lowest efficiency scores are Greece and Cyprus. The positive conclusion is that countries efficiency mainly has an ascending trend. Furthermore, the second stage analysis showed that resource productivity, private investments, jobs and gross value added related to the circular economy sector and GDP per capita significantly influence the efficiency of circular economy performance.